Automator for Mac OS X 10.6 Snow Leopard - Waldie, Ben (Visual quickstart guide., 2010)
A guide for Mac users on the features and functions of Automator covers such topics as workflow creation, working with actions, recording manual events, customizing Automator, looping, using variables, and plug-ins.